2014
DOI: 10.1073/pnas.1415178111
|View full text |Cite
|
Sign up to set email alerts
|

BID mediates selective killing of APC-deficient cells in intestinal tumor suppression by nonsteroidal antiinflammatory drugs

Abstract: Colorectal tumorigenesis is driven by genetic alterations in the adenomatous polyposis coli (APC) tumor suppressor pathway and effectively inhibited by nonsteroidal antiinflammatory drugs (NSAIDs). However, how NSAIDs prevent colorectal tumorigenesis has remained obscure. We found that the extrinsic apoptotic pathway and the BH3 interacting-domain death agonist (BID) are activated in adenomas from NSAID-treated patients. Loss of BID abolishes NSAID-mediated tumor suppression, survival benefit, and apoptosis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 35 publications
2
45
0
Order By: Relevance
“…5 As n-3 PUFA 27 and curcumin 28 promote apoptosis in 1,2-dimethylhydrazine or AOM-injected rats, we next investigated the synergistic effects of n-3 PUFA+curcumin on the Lgr5 + stem cell acute DNA damage response. Figure 1b shows representative colocalization images of DNA-damaged ( γ H2AX, white) Lgr5 + stem cells (GFP, green) with apoptosis (TUNEL, red), DNA repair (MGMT, red) or cell proliferation (EdU, red).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 As n-3 PUFA 27 and curcumin 28 promote apoptosis in 1,2-dimethylhydrazine or AOM-injected rats, we next investigated the synergistic effects of n-3 PUFA+curcumin on the Lgr5 + stem cell acute DNA damage response. Figure 1b shows representative colocalization images of DNA-damaged ( γ H2AX, white) Lgr5 + stem cells (GFP, green) with apoptosis (TUNEL, red), DNA repair (MGMT, red) or cell proliferation (EdU, red).…”
Section: Resultsmentioning
confidence: 99%
“…For example, it has been shown that nonsteroidal anti-inflammatory drugs (NSAIDs) can induce apoptosis in Lgr5 + stem cells and suppress adenoma formation in APC Min/+ mice. 5 Long-term use of NSAIDs, in particular COX-2-specific inhibitors, is associated with side effects, which has stimulated the development of new targets and combination strategies for cancer chemoprevention. 6 …”
mentioning
confidence: 99%
“…These targets may contribute to NSAID anti-inflammatory mechanisms, applications, and the occurrence of adverse drug reactions (Lounkine et al, 2012). Reported NSAID functions include inhibition of NF-κB, inhibition of proteasome function, activation of intrinsic and extrinsic pathways of apoptosis, cell cycle arrest, and activation of stress kinases (Jana, 2008; Leibowitz et al, 2014). However, many of these effects are seen only at superphysiological concentrations, limiting their biological relevance (Ghosh et al, 2015; Mehlisch and Sykes, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…While previous research has observed pro-apoptotic and chemoprotective NSAID behaviors, these studies were not conducted under inflammatory conditions, which are more relevant to patient physiology (Jana, 2008; Leibowitz et al, 2014). This approach masks the independent contributions of caspases, which are upregulated under inflammatory conditions, and suggests that environment may affect the NSAID anti-inflammatory mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the combination of doxorubicin and SAHA triggers the apoptosis by downregulating Bcl-2 The treatment options for CRC are limited and it develops due to the inactivation of APC gene (adenomatous polyposis coli), which is involved in tumor suppressor pathway. Leibowitz and co-workers have demonstrated that NSAIDs kill non-functional APC-harboring intestinal stem cells that protect against the development of colon cancer [73]. However, the mechanism behind this is unclear but it was identified that BID and extrinsic apoptotic pathway were activated in adenomas of NSAID-treated patients.…”
Section: A Kamal Et Almentioning
confidence: 99%